A new species of spectacularly coloured flat lizard Platysaurus (Squamata: Cordylidae: Platysaurinae) from southern Africa - Whiting, Martin J.; Branch, William R.; Pepper, Mitzy; Keogh, J. Scott (Zootaxa, 2015)
We describe a new species of flat lizard (Platysaurus attenboroughi sp. nov.) from the Richtersveld of the Northern Cape Province of South Africa and the Fish River Canyon region of southern Namibia. This species was formerly confused with P. capensis from the Kamiesberg region of Namaqualand, South Africa. Genetic analysis based on one mtDNA and two nDNA loci found Platysaurus attenboroughi sp. nov. to be genetically divergent from P. capensis and these species can also be differentiated by a number of scalation characters, coloration and their allopatric distributions. To stabilize the taxonomy the type locality of Platysaurus capensis A. Smith 1844 is restricted to the Kamiesberg region, Namaqualand, Northern Cape Province, South Africa.